THE CORRELATION BETWEEN SUSTAINABLE PERFORMANCE MEASURES AND ORGANIZATIONAL SUSTAINABILITY IN THE BRAZILIAN CONTEXT - RODRIGO GOYANNES GUSMÃO CAIADO; OSVALDO LUIZ GONÇALVES QUELHAS (Analele Universităţii Constantin Brâncuşi din Târgu Jiu : Seria Economie, 2016)
Over the past few years, issues of sustainability are gaining greater prominence among organizations and their stakeholders around the world and with it the effective measurement of environmental performance has been a challenge for sustainable transition. The purpose of the article is to analyse, through the the perception of market experts and researchers, what sustainable performance measures have stronger positive correlation to achieve organizational sustainability in order to help employees in making decisions that reduce the consumption of resources and that create value throughout its chain. The research is of an exploratory and descriptive nature, with qualitative and quantitative method and has a deductive logic. It aims to help professionals and academics who want to start the measurement and continuous improvement of economic, environmental, social, governance and technical performance of their organizations. Finally, the analyzes allow direct efforts to sustainable measures considered most important, allowing the transition of the organization for sustainability.